Chemical constituents from Dictamnus dasycarpus Turcz. (December 2020) - Yan, Yahui; Liu, Xin; Zhang, Lingxiao; Wang, Yu; Chen, Qili; Chen, Zaixing; Xu, Liang; Liu, Tao
Abstract: Fifteen compounds (1 –15 ) were isolated from Dictamnus dasycarpus Turcz. The structures of all compounds were elucidated on the basis of spectroscopic data. Their structures were identified as dictamnine (1 ), skimmianine (2 ), haplopine (3 ), γ-fagarine (4 ), dasycarine (5 ), glycolone (6 ), 8, 9-dimethoxygeibalansine (7 ), 7, 8-dimethoxymyrtopsine (8 ), 8-methoxyflindersine (9 ), 3-formylindole (10 ), kihadanin A (11 ), fraxinellone (12 ), β-sitosterol (13 ), radicol (14 ), and magnolol (15 ). Among them, compounds 10 and 15 were isolated for the first time in the genus Dictamnus and this is the first report of the presence of compound 14 in the Dictamni dasycarpus Turcz. Highlights: Fifteen compounds were isolated from the root barks of Dictamnus dasycarpus Turcz. Compounds 10 and 15 were isolated for the first time in the genus Dictamnus. Compound 14 was firstly isolated from Dictamnus dasycarpus Turcz. The significance of chemotaxonomy for these compounds was discussed.